Stem cell-derived polarized hepatocytes - Viet Loan Dao Thi (Nature Portfolio, 2020)
To model hepatocyte function accurately in vitro, it is necessary to generate and maintain a polarized epithelium. Here, the authors describe a protocol to generate polarized human pluripotent stem cell-derived hepatocyte-like cells (HLCs) to model enteric virus production and drug secretion in vitro.